Kajian Keberhasilan Implementasi Kebijakan Online Single Submission Risk Based Approach (OSS-RBA) di DPMPTSP Kabupaten Ketapang pada Perusahaan Perkebunan - Lubis, Bambang Irwansyah; Krisdiarto, Andreas Wahyu; Listyani, Listyani (Politeknik Negeri Lampung, 2024)
Online Single Submission Risk Based Approach (OSS-RBA) is a risk-based business licensing service system that is carried out online. It is important to know about the application of the OSS-RBA Policy because it relates to the country's national achievements in simplifying the business licensing process and attracting foreign investors. The plantation business sector, especially oil palm, is important to pay attention to. The high contribution of the country's foreign exchange originating from this industry is one of the reasons the government has made the business licensing process smooth. For this reason, this research aims to measure the level of success in implementing the OSS-RBA Policy in the Investment and One-Stop Integrated Services Service (DPMPTSP) Ketapang Regency, especially in plantation companies. This research uses a mixed method with purposive sampling. In this study, respondents were divided into two groups, specifically 4 respondents from the policy implementer and 35 respondents from the oil palm plantation company. The George Edward III Policy Implementation Model used theory, which determined four indicators that influence implementation: communication, resources, disposition, and bureaucratic structure. The research on communication indicators showed that there had been a clear and consistent transmission of information from policymakers to policy implementers and business actors. Meanwhile, equipment and authority resources have been fulfilled in the resource indicators. For disposition, licensing services have been provided optimally. Finally, regarding bureaucratic structure indicators, DPMPTSP Ketapang Regency has done SOPs for services and licensing activities.